Komunikasi Interprofesional Sebagai Upaya Pengembangan Kolaborasi Interprofesi Di Rumah Sakit: Systematic Review - Yunis Veronika Purba; Anggorowati Anggorowati (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2018)
Interprofessional communication is very important in today's health services, where it can expand the population of health services especially in providing care in health services. Effective interprofessional communication is an important skill that can improve the function of high-quality teams in the care of patients by involving several scientific disciplines such as doctors, nurses and other health teams (interprofessional collaboration). The purpose of systematic review is to find out whether interprofessional communication can develop interprofessional collaborative efforts in hospitals. The method used was a systematic review. The articles were searched through Google Scholar, Proquest, Science Direct, are done using advanced in accordance with the keywords Professional, Communication, Collaboration. There were 3 articles in which each article produced that interprofessional communication can develop interprofessional collaboration in hospitals, with effective interprofessional communication, nurses, doctors and other health teams can respect each other and have the same vision and mission in providing services to clients to improve service quality and satisfaction for the clients themselves.